Šumerskij kosmogoničeskij mif «Putešestvie Ninurty v Eredy» (Biblioteka Nippura, XIX-XVII vv. do n.e.) - Emel'janov, Vladimir V. (Gs Vinogradov)
engl. Resümee: The Sumerian Mythological Text «Ninurta's Journey to Eridu» (The Nippur library XIX-XVII B.C.)